DIGITALIZATION AS A BASE OF ACCELERATED TECHNOLOGICAL MODERNIZATION OF KAZAKHSTAN ECONOMY - Nyurlikhina G.; Sujubaeva S.; Nurlikhin A.; Matkarimova L. (Academic Journal of Physical and Chemical Sciences, 2020)
The topicality of the paper is stipulated by active penetration of digital technologies to all spheres of contemporary society life. The corporative and governmental structures of the world including the Republic of Kazakhstan have aware the necessity of digital transformation of economy to enhance the competitiveness in the global digital space. The methodic of the research is based on application of common scientific principles of system approach; methods of logical, factor, comparative, strategic, managerial analysis; quantitative and qualitative investigation of the main tendencies and fields of forming and development of informational-communication and digital infrastructures. The paper is aimed at analysis of the state and problems of digital development of Kazakhstan and elaboration of recommendations on digitalization development. To achieve the set goal the contemporary tendencies of digitalization development of economics and society were revealed, the analysis of precursors and conditions of digital economics development were analyzed as well as related sectors favoring the digitalization of economics. The experience of the developed and developing countries that achieved successful results in the process of economics digitalization was studied regarding revealing the possibilities to apply its experience for Kazakhstan. The adequate research conclusions were made, and the recommendations on digital development of the country were suggested.